Alexithymia as a moderator of the relation between self-care and psychological distress - Mohammad Abassi; Fatemeh Rezaei (Gonabad University of Medical Sciences, 2019)
Alexithymia is considered as important contributor in the psychological distress. This study examined the moderator role of alexithymia in the relationship between self-care and psychological distress in 217 elementary school teachers. Alexithymia, self-care and psychological distress has been assessed in 217 teachers (108 females and 109 males). Participants were asked to complete 4 including socio-demographic questionnaire, toronto alexithymia scale, health-promoting lifestyle profile II, and the depression, anxiety, and stress scales. Results revealed that there is a significant relationship between self-care, alexithymia and psychological distress. Alexithymia was also a moderator in the relationship between self-care and psychological distress. The findings supported the hypothesis that higher levels of alexithymia would be associated with higher levels of psychological distress, and that lower levels of alexithymia would be associated with lower levels of psychological distress. Alexithymia helped explain the self-care and psychological distress link in adults.